Pemberdayaan UMKM Melalui Transformasi Digital: Meningkatkan Daya Saing Roti Bakar Bahagia di Sektor Kuliner Indonesia - Alexio Manuelo; Bella Vista; Catherine Patricia; Della Vista; Ervina Leonita; Lulu Meiliani Orlando; Maria Jesica Octariani; Santi Rimadias (Lembaga Pengembangan Kinerja Dosen, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in encouraging economic equity in Indonesia by encouraging economic growth, encouraging innovation and creativity, and reducing unemployment. Among the various MSME sectors, the culinary business stands out because it is very promising due to the universal food needs. One of the culinary businesses, Roti Bakar Bahagia, located in Medang Lestari, Tangerang Regency, shows significant growth potential but faces challenges in optimizing digital marketing and payment systems. To overcome these challenges, community service activities are carried out to increase the digital presence and digital payment infrastructure of the business. The assistance provided includes designing and making logos, designing and recreating menu lists, creating Google Maps lists, and integrating digital payment systems through QRIS. These efforts proved to be very beneficial, equipping Roti Bakar Bahagia to increase its competitiveness and sustain growth in the dynamic culinary market.